Defining chaperone-usher fimbriae repertoire in Serratia marcescens. (May 2021) - González-Montalvo, Martín A.; Tavares-Carreón, Faviola; González, Gloria M.; Villanueva-Lozano, Hiram; García-Romero, Inmaculada; Zomosa-Signoret, Viviana C.; Valvano, Miguel A.; Andrade, Angel
Abstract: Chaperone-usher (CU) fimbriae are surface organelles particularly prevalent among the Enterobacteriaceae . Mainly associated to their adhesive properties, CU fimbriae play key roles in biofilm formation and host cell interactions. Little is known about the fimbriome composition of the opportunistic human pathogen Serratia marcescens . Here, by using a search based on consensus fimbrial usher protein (FUP) sequences, we identified 421 FUPs across 39 S. marcescens genomes. Further analysis of the FUP-containing loci allowed us to classify them into 20 conserved CU operons, 6 of which form the S. marcescens core CU fimbriome. A new systematic nomenclature is proposed according to FUP sequence phylogeny. We also established an in vivo transcriptional assay comparing CU promoter expression between an environmental and a clinical isolate of S. marcescens, which revealed that promoters from 3 core CU operons (referred as fgov, fpo, and fps ) are predominantly expressed in the two strains and might represent key core adhesion appendages contributing to S. marcescens pathogenesis. Highlights: Genomic analysis of Serratia marcescens revealed 20 conserved chaperone-usher (CU) fimbriae. Six highly conserved clusters compose the core CU fimbriome of S. marcescens. A CU nomenclature is proposed according to S. marcescens usher proteins phylogeny. Core operons fgov, fpo, and fps are highly expressed in S. marcescens isolates.